An unusual presentation of Burkitt lymphoma as a neck mass in immunocompetent adult male: a case report - D., Jayapriya; P., Ayishwarrya; T. C., Vikram Raj Mohanam; S., Kalaiarasan; P., Dilshada; D., Roshan; Bage, Atul Mukul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Burkitt lymphoma (BL) is a highly aggressive B-cell non-Hodgkin lymphoma defined by MYC gene translocation. The World Health Organization (WHO) and International Consensus Classification (ICC) recognize BL and Burkitt leukemia as manifestations of the same disease and differentiate BL from other high-grade B-cell lymphomas. The three clinical types-endemic, sporadic, and immunodeficiency-related-show differing geographic distributions and presentations. We report and unusual presentation of BL presenting as a left sided neck mass in a immunocompetent adult male. This case highlights the aggressive nature of BL and the importance of early and accurate diagnosis of through imaging and biopsy.